Knowledge of the university teaching and Gnosiological Cycle in Paulo Freire: tessitures from the Graduate Education (Olhar de Professor, 2020)
This article presents results of a doctoral research between 2016 and 2020 that aims to understand from the ontology, epistemology and pedagogical praxis the dialectic of the approaches and / or distances of the knowledge of university teaching in relation to the Gnosiological Cycle in Paulo Freire. This is an ethnomethodological study with a qualitative approach, based on scientific bricolage as an investigative posture. Bibliographic research, document analysis, on-line questionnaire, interview based on hypothetical teaching cases and the explanation interview were the data collection techniques experienced with six masters and doctors graduated from the Graduate Program in Education at the State University of Ceará (PPGE-UECE) between 2004 and 2017. The findings pointed out that the Freirean Gnosiological Cycle contributes to thinking and promoting the constitution of university teaching knowledge based on do-discourse, research and intersubjective dialogue.
Keywords: Knowledge of university teaching. Gnosiological Cycle in Paulo Freire. Post-Graduation in Education.